The Impact of TikTok Social Media Utilization as a Promotional Tool on Revenue Growth of Micro, Small, and Medium Enterprises (MSMEs) - Muh. Ramli; Rusli; Hasrul Wijaya; Safri Tahir (Universitas Muhammadiyah Makassar, 2026)
The rapid expansion of digital marketing has transformed how Micro, Small, and Medium Enterprises (MSMEs) promote products, particularly through short-video platforms such as TikTok. Despite widespread adoption, empirical evidence on how platform utilization contributes to income growth among local MSMEs remains limited. This study aimed to examine the effect of short-video social media utilization as a promotional strategy on MSME revenue growth in the Manakarra Beach area of Mamuju City, Indonesia. The research employed a quantitative correlational design using a cross-sectional approach. The population consisted of 50 MSME actors, and total sampling was applied. Primary data were collected through structured questionnaires measuring promotional intensity and income changes, and the data were analyzed using simple linear regression. The results showed that digital promotion through short-video content had a positive and statistically significant effect on MSME income (t = 2.688; p = 0.010 < 0.05). The regression coefficient indicated that increased promotional utilization contributed positively to revenue improvement, although the coefficient of determination (R² = 0.131) revealed that only 13.1% of income variation was explained by the model, with the remainder influenced by other business factors. These findings indicate that short-video social media functions as an effective complementary marketing instrument rather than a single determinant of business performance. This study contributes to digital marketing and MSME development literature by providing empirical evidence on the economic relevance of interactive promotional media and suggests that integrated marketing strategies and content optimization are essential for maximizing MSME revenue growth.